(3eaJGM GdhUhd TQM ebOeI GdGUhds - (3GdaGSj , eMeO Hf YHO GdbGOQ Hf Ydj Hf jhSa, CHh YHO Gddg,J (B1116 (3g` s ((3eMeO Hf MeRg Hf YHOGddgs)
(3ChdgG (B:s
(3hHYO ajbhd GdYH GdabjQ Edi Yah QHg hSejJg eaGM GdhUhd s
(3BNQgG (B:s
(3LeY eUdMI GdeQSdg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3CUhd Gdabgs